7. The Burke's Pentad Heuristic: Potentiality for Creative Idea Generation in Graphic Communication Design - Ebigbagha Sylvester Zifegha (Sciendo, 2020)
The Burke's Pentad (Act, Agent, Agency, Scene and Purpose) is a creative idea generation guide for dramatism (or dramatistic framework). Its utilization to probe, often engenders a process of stochastic combination, whereby a vista of multiple ideational variations emerge in one's mind, from which an appropriate subset could be selected and implemented. This usually affords inspiration, creative flow and energy that are pivotal for success in drama as much as in visual communication. However, there is prevalent unawareness of the potentials of the Pentad model as a veritable structure to creating innovative ideas in art and design. Therefore, this paper focused on the potentiality of the Pentad for creating and or analyzing ideas on form generation for pedagogical, practical, or theoretical purpose in graphic communication design. Towards this end, a triangulation of methods: critical-historical-analytic examination, artistic exploration, and content analysis are employed. The paper introduced the reader to the need for a strategy to generate new ideas, stimulate creative thinking, and enhance self-motivation in visual expression for structural and human development. Furthermore, it highlighted the processes of creativity, and form generation for material culture development. Also, the paper discussed the Pentad and its utilization for generating new ideas in art/design. It was found that the Pentad is indispensable in generating ideas for creating, interpreting and teaching visual form. The paper ended with the need for visual communicators to be acquainted by use of the Pentad for creative ideas to generate product with satisfactory outcomes.